Policies to combat nitrogen pollution in South Asia: gaps and opportunities. (28th January 2022) - Yang, Anastasia L; Raghuram, Nandula; Adhya, Tapan Kumar; Porter, Stephen D; Panda, Ananta Narayan; Kaushik, Himadri; Jayaweera, Anuradha; Nissanka, Sarath Premalal; Anik, Asif Reza; Shifa, Sharmin; Sharna, Shaima Chowdhury; Joshi, Rajendra; et al.
Abstract: Assessing and managing nitrogen sustainably is imperative for achieving the 17 UN Sustainable Development Goals (SDGs) targeted for 2030. South Asian countries, aware of the environmental and health impacts of nitrogen pollution, regionally as well as globally, piloted the 2019 UN resolution on sustainable nitrogen management, calling for urgent policy action. This paper assists South Asia policy development by providing new insights into nitrogen-related policies in the region; it makes a step-change advance on an existing global analysis and database. We built on available methods to better identify, classify and analyse 966 nitrogen-related policies for the region. We compared the global and regional nitrogen policy landscapes to explain the benefits of a deeper policy assessment. The policies we classified as having 'higher' relevance—those with direct reference to nitrogen and/or its potential impacts—represent the current nitrogen policy landscape for South Asia. We show that a small proportion of policies (9%) consider multiple pollution sources, sectors, nitrogen threats and impacts, with integrative policy instruments. A 5% of policies also consider both non-point and point sources of pollution, representing standout policies. More such policies with an integrated approach are vital in addressing the complexities of nitrogen pollution. Adapting existing and drafting new policies are both required to deal with other current and emerging nitrogen issues. Our analysis provides evidence for a roadmap for sustainable nitrogen policy in South Asia and beyond and supports efforts to reduce the threats posed by nitrogen pollution to achieve the SDGs.